Perbandingan Kekuatan Tarik antara Stranded Fiber dengan Braided Fiber pada Fiber Reinforced Composite Jenis Ultra High Molecular Weight Polyethylene (UHMWPE) - Prihashinta Uswatun Hasanah; Purwanto Agustiono; Widjijono Widjijono (Jurnal Material Kedokteran Gigi, 2018)
Fiber reinforced composite (FRC) is a material that has at least two components were matrix and fiber. Difference of fiber architecture on the FRC may affect the mechanical strength of FRC. Stranded and braided fiber fiber is one of materials that are commonly used in dentistry, both have differences from the sides of the fiber arcitecture. This research aims to know the comparative tensile strength between fiber stranded with braided fiber on FRC type of UHMWPE. This research uses 8 samples were divided into 2 groups. The types of UHMWPE fiber with braided fiber (Construct TM, Kerr, USA) and stranded fiber (Biodental TM, Australia). The sample is 20x10x2mm according ASTM 638M. Tensile strength is measured by using a universal testing machine. Tensile strength data then tested using the indepedent t-test. The results showed the tensile strength fiber and fiber braided stranded i.e. of 35.65 ± 2.538 MPa and 49.43 ± 2.953 MPa. Independent t-test results test shows there is difference significantly in tensile strength between fiber and fiber braided stranded (p < 0.05). The conclusion of the research was there stranded fiber tensile strength higher than with braided fiber on FRC type of UHMWPE.